Pengukuran Daya Terima BTS 4G Pada Kondisi Hujan Dengan Metode Coordinated Scheduling/Interference avoidance - Yadnya, Made Sutha; Wedarama, I.G.P. Wedashwara; Sudiarta, I Wayan (LPPM Universitas Mataram, 2024)
The quality of signal reception from the Base Transceiver Station (BTS) which is still installed is the highest on the 4G VoLTE network from the provider provider within the coverage area of the Mataram University Campus is still fluctuating. This needs to be carefully monitored so that users can surf the internet or use IoT facilities properly according to access requirements. data transfer needs... Conditions due to environmental disturbances such as rain are also disrupted. This requires accurate measurements, this research is done with the help of software installed on the user according to their moving position along the existing road access. The measurement results were obtained in rainy and clear sky conditions and it was found that differences and cell movement were disturbed. Recommendations to providers in this paper are input for improving the quality of providers in the Mataram University area.